n vitro H1-receptor antagonist activity of methanolic extract of tuber of Stephania glabra - Nisar Ahmad Khan, Dinesh Kumar, Zulfiqar Ali Bhat, Vijender Kumar, Navneet Nagpal and Santosh S. Bhujbal (Bangladesh Pharmacological Society, 2010)
In the present study, methanolic extract of tuber of Stephania glabra was evaluated for H1-bloker activity by employing in vitro screening models of guinea pig ileum and goat tracheal chain preparation. Goat isolated trachea and guinea pig ileum contracted to histamine in a dose-dependent manner while chlorpheniramine blocked this effect. The methanolic extract produced significant dose-dependent H1-receptor antagonist activity by blocking histamine-induced contraction.